Determinants of tax compliance intention: a review of non-economic factors - Noral Hidayah Alwi; Zahir Osman; Sellywati Faizal (2022)
Taxes are the primary source of income for the government. Tax collection is the most reliable method of fostering national development. In order to collect the correct amount of total national tax income, taxpayer compliance must occur. Because of this, any kind of tax non-compliance activity could result in large losses for the government. Tax compliance issues have received a lot of attention from scholars over the past few decades due to the pressing requirement to make sure that the tax revenue is sufficient to cover the budgeted national spending. This prompted thorough and in-depth examinations that exposed various viewpoints. Based on this, this research study examines the prior literature on the non-economic factors of tax compliance issues in order to emphasise the scope, methodology, and models employed by earlier researchers in order to identify research gaps and suggest those for future studies. Previous research's scope, geographic location, theories/models, and technique were all analysed to help with understanding the topic at hand. The report has also highlighted and made recommendations for important areas where future research should focus. Finally, it has identified the patterns of earlier studies with reference to these three elements.